Similar simulation study on the characteristics of the electric potential response to coal mining. (19th December 2017) - Niu, Yue; Li, Zhonghui; Kong, Biao; Wang, Enyuan; Lou, Quan; Qiu, Liming; Kong, Xiangguo; Wang, Jiali; Dong, Mingfu; Li, Baolin
Abstract: An electric potential (EP) can be generated during the failure process of coal and rock. In this article, a similar physical model of coal rock was built and the characteristics of the EP responding to the process of coal mining were studied. The results showed that, at the early mining stage, the structure of coal rock strata were stable in the simulation model, the support stress of overlying coal rock strata was low and the maximum subsidence was little, while the EP change was less. With the advancement of the working face, the support stress of the overlying coal rock strata in the mined-out area changed dramatically, the maximum subsidence increased constantly, the deformation and destruction were aggravated, and cracks expanded continuously. Meanwhile, the EP response was significant with fluctuation. When significant macro damage appeared in coal rock strata, the EP signal fluctuation was violent. The overlying coal rock strata were influenced by gravity and mining activity. During the mining process, the crack growth and the friction, together with slip between coal and rock particles, resulted in the response of EP. The change in EP was closely related to the damage state and stress distribution of the coal rock strata. EP monitoring has the advantages of accurate reflection and strong anti-interference in the field. Therefore, with further study, an EP monitoring method could be applied for monitoring and early warning of coal and rock dynamic disaster, and risk evaluation in the future. The strength of the EP and its fluctuation degree could serve as the key discrimination indexes.